Study of CEO Narcissism and Corporate R&D Investment - Wang, Linan; Li, Huiying; Mu, Yinghan (Frontiers in Psychology, 2022)
Narcissism is a deep-rooted personality trait that is particularly common in corporate leaders, and narcissistic leaders have a noticeable influence on the R&D investment behavior of enterprises. This paper empirically examines the effect of CEO narcissism on R&D investment and the moderating effects of financing constraints, and the nature of corporate ownership based on the Upper Echelons Theory, using the CEO signature size as a measure of CEO narcissism for the 2007–2020 Chinese A-share listed companies. The results show that CEO narcissism has a significant negative effect on R&D investment; corporate financing constraints play a negative moderating role between CEO narcissism and R&D investment, and the negative effect of CEO narcissism on corporate R&D investment is more significant in non-state-owned firms than in state-owned firms. The study's findings enrich and expand the theory related to CEO narcissism and have important practical implications for R&D investment decisions and the choice of corporate executives in China.